3D Porous Pyramid Heterostructure Array Realizing Efficient Photo‐Electrochemical Performance. Issue 5 (26th November 2019) - Cao, Shuyan; Wu, Yunzhen; Hou, Jungang; Zhang, Bo; Li, Zhuwei; Nie, Xiaowa; Sun, Licheng
Abstract: Direct photo‐electrochemical (PEC) water splitting is of great practical interest for developing a sustainable energy systems, but remains a big challenge owing to sluggish charge separation, low efficiency, and poor stability. Herein, a 3D porous In2 O3 /In2 S3 pyramid heterostructure array on a fluorine‐doped tin oxide substrate is fabricated by an ion exchange–induced synthesis strategy. Based on the synergistic structural and electronic modulations from density functional theory calculations and experimental observations, 3D porous In2 O3 /In2 S3 photoanode by the protective layer delivers a low onset potential of ≈0.02 V versus reversible hydrogen electrode (RHE), the highest photocurrent density of 8.2 mA cm −2 at 1.23 V versus RHE among all the In2 S3 photoanodes reported to date, an incident photon‐to‐current efficiency of 76% at 400 nm, and high stability over 20 h for PEC water splitting are reported. This work provides an alternative promising prototype for the design and construction of novel heterostructures in robust PEC water splitting applications. Abstract : A 3D porous In2 O3 /In2 S3 pyramid array is fabricated by an ion exchange–induced strategy. Based on synergistic structural and electronic modulations, the 3D protective In2 O3 /In2 S3 photoanode delivers the highest photocurrent of 8.2 mA cm −2 at 1.23 V vs reversible hydrogen electrode (RHE) and stability for photo‐electrochemical (PEC) water splitting among all the In2 S3 photoanodes reported to date.